Analysis of instant and long-term performance of timber-concrete floors with boundary conditions other than simply supported. (1st March 2022) - Adema, Andrés; Santa María, Hernán; Guindos, Pablo
Abstract: This paper describes an analytical procedure for designing timber-concrete composites (TCC) subjected to boundary conditions other than simply supported. Currently available investigations of TCCs are mainly focused on simply supported slabs, as it is a typical configuration for timber buildings. However, in other structural applications, and remarkably for reinforced concrete buildings, the boundary conditions of the TCC slabs are not likely to be simply supported. Such distinct boundary conditions can significantly reduce the cross section height, mid-span deflection and self weight of the structure, the last one being crucial in seismic regions. The proposed procedure is derived from two simplified methods available in the literature, one general in its nature while the other being valid for simply supported beams. The short-term analytical model was compared against finite element models (FEM) and to the only experimental investigation on partially restrained TCCs available in the literature, while the long-term analytical model was compared only against FEM. At the end of the investigation, a full-scale continuous TCC beam was tested in the serviceability range, to compare with the prediction of the proposed analytical model. The model underestimated the mid-span deflection at 4.5 kN by 13%, concluding that the proposed simplified procedure is valid for boundary conditions other than simply supported. Further experimental campaigns are needed in the future to assess the versatility of the model in a wider range of boundary conditions, including short-term and long-term tests, which should enhance the applicability of TCC slabs in structures different from timber buildings and bridges. Highlights: Analytical procedure was validated with numerical models and experimental results. TCC continuous beam was tested in the serviceability range. Linear and non-linear FE models were made for a propped-cantilever TCC.